Pre-Formulation Study for Palatable Microbeads of Lycopene - Rahman, Yasir; Amin, Saima; Mir, Showkat R; Kohli, Kanchan (Journal of Drug Delivery and Therapeutics, 2019)
Lycopene is a widely used nutraceuticals for its antioxidant property but the molecule has poor aqueous solubility, high instability, and extremely low intestinal permeability leading to its poor bioavailability. In the present study, pre-formulation study was carried out to prepare sodium alginate microbeads with the intention to deliver an effective amount of lycopene for high absorption through oral route. A thorough physical characterization and spectral analysis were done to understand the characteristic of lycopene such as its melting point, UV spectrophotometric analysis, chromatography through reverse phase HPLC. Fourier transform infrared spectroscopy and differential scanning calorimetry were adopted to know the interaction of sodium alginate with lycopene. Box-Behnken design (version 9.0.2.0, Stat Ease Inc, USA) was used to analyse the effect of formulation variables such as sodium alginate (%), glutaraldehyde (%) and stirring speed on lycopene entrapment and its loading into microbeads. The adopted preformulation strategy revealed that lycopene was a crystalline powder with a sharp melting point at 155oC and the prominent functional groups were present in the sample. UV and HPLC analysis revealed precise quantitation and authenticity of lycopene. Excipient compatibility also revealed inertness of sodium alginate. Response surface morphology revealed significant effect of alginate, glutaraldehyde and stirring speed on formation of best composition. Therefore, it is concluded that lycopene can be formulated as microbeads for oral drug delivery. Keywords: lycopene, sodium alginate, permeation, absorption, microbeads